Pelatihan Media Pembelajaran berbasis Audio Visual bagi Guru PJOK Kabupaten Polman - Muh. Ilham Aksir; Hasyim; Hasmyati; Harnita Rosalia; Muhammad Akbar Syafruddin (PT. Mediatama Zayna Indonesia, 2025)
Teaching is a systematic and efficient method of making the right decisions. This includes decision making regarding content, methodology, duration, student grouping, questioning techniques, follow-up questions, and the review process in the context of teaching. Community service activities aim to conduct audio-visual-based learning media training for physical education, sports, and health (PJOK) teachers in Polewali Mandar Regency. The audio-visual-based learning media training activity uses a mentoring method. Participants in this activity were 50 Physical Education and Sports teachers in Polewali Mandar Regency. To solve the problem of the lack of teacher understanding in creating effective learning media for improving student learning outcomes, the team provided a solution by providing audio-visual-based teaching material training which was carried out through stages of activities consisting of socialization stages, training stages, and evaluation stages. The targeted outputs after the implementation of this activity were that PJOK teachers in Polewali Mandar understood the appropriate learning media given according to student needs, understood the benefits of audio-visual media, and understood how to compile audio-visual-based teaching materials.